Investigating enteric bacterial pathogens in Ile-Ife, South-West Nigeria - Aaron Aboderin (The Journal of Infection in Developing Countries, 2007)
I teach medical microbiology to both undergraduate and postgraduate students at Obafemi Awolowo University. The program has an average of 250 medical students each session, in addition to students in Nursing Science and Pharmacy. At the same time, I am engaged as a Consultant in Clinical Microbiology at the Obafemi Awolowo University Teaching Hospitals Complex (OAUTHC). OAUTHC is one of the tertiary health institutions in Nigeria, providing health care services as well as training for the development of health-delivery manpower. Component units of OAUTHC include the Wesley Guild Hospital, a 212-bed unit, and a 364-bed Ife Hospital Unit.